Hiring labourers for the vineyard and making sense of God"s grace at work: An empirical investigation in hermeneutical theory and ordinary theology - Francis, Leslie J. (HTS teologiese studies, 2022)
The Matthean parable of the labourers in the vineyard is open to multiple interpretations. For some, the parable may speak of God’s unlimited grace and generosity; for others the parable may speak of God’s unfairness. The present study is set within the context of an emerging interest in the concept of grace as a topic for empirical enquiry. The study draws on the theoretical framework provided by the notion of ordinary theology and employs the sensing, intuition, feeling and thinking (SIFT) approach to biblical hermeneutics, which is rooted in Jungian psychological type theory. Data were drawn from two one-day workshops with Church of England Readers (lay ministers). On each occasion the participants were divided into three separate groups according to their preferences for thinking or feeling (the two judging functions proposed by psychological type theory) and within these groups they were invited to explore the messages about grace in Matthew 20:1–15 (Jesus’ parable of the labourers in the vineyard). The rich data gathered from these workshops generated insights into contemporary theologies of grace and also confirmed the hypothesis that a biblical interpretation of grace is shaped by the reader’s psychological type preference for thinking or feeling. While feeling types tended to empathise, thinking types pondered motives and unfairness.Contribution: Situated within the reader perspective approach to biblical hermeneutics, the SIFT method is concerned with identifying the influence of the psychological type of the reader in shaping the interpretation of sacred text. Employing this method, the present study contributes to three fields of scholarship: to the field of homiletics and hermeneutics, to the field of ordinary theology and to the emerging field concerned with the concept of grace as a topic for empirical enquiry.